Strategi Menumbuhkan Wirausaha Kecil Menengah yang Tangguh - Tejo Nurseto (Universitas Negeri Yogyakarta, 2004)
UKM sector is a economic rescuer sector during Indonesia crisis and creates public and government new awareness of its important of UKM as well as informal sector. UKM faces some problems including: (1) education, motivation and technology problems, (2) production problems, (3) marketing problem, (4) financial problem, (4) less conducive business environment. UKM business development needs SWOT analysis to diagnose internal and external factors. It is needed to identify product characteristic, market, technology, capital and human resources necessity and managerial aspect.